Determinación de la carga sedimentaria de la parte alta de la cuenca del Río Napo, Provincia Napo, periodo 2019-2020. - Espejo Almachi, Guadalupe Fernanda (2020)
The sedimentary load of a river channel is the amount of material carried by the flow that affects the quality of the waters, increasing this problem in times of high rainfall that generate floods and possible floods in the channel, which damages and affects the banks of Napo River tributaries. The investigation determined the sedimentary load of the hydrological stations found in the upper part of Napo river basin. Using the hydrological data from INAMHI and Hydraccess V. 6.2 software, a database of flow, heights, gauges and calibrations of 12 hydrological stations was created. Through this process, the graphs of the solid waste curve were obtained as a function of liquid waste, which allowed to determine environmental degradation, with correlation coefficients higher than 0.70 and correlation higher than 80%, with the exception of stations H0714, H0721 and H0733. The results of the gauging samples carried out at LANCAS on concentration and solid flow (sediment) determined that the highest (3212kg / s) and lowest (0.222kg / s) solid flow is found at Jatunyacu DJ Iloculin station (H0721) and Yanahurco DJ Valle (H0722) respectively. With regard to sediments concentration, the Coca Codo Sinclair station (H0735) is the most eroded due its high content of suspended solids (0.465 kg / m3), followed by Jatunyacu Dj Iloculin station (0.389 kg / m3) and Coca in San Rafael (0.308kg / m3). The Salado AJ Coca station (H0728) is the one that contributes to the greatest amount of sediment to Coca river with a value of 2688.5 t / year / km2, it drags the suspended material through torrents that occurs in the flow path and the station with the lowest concentration is Yanahurco DJ Valle (H0722) with a value of 30.51 t / year / km2. In addition, the correlation graphs between solid waste and liquid waste could determine that, there is environmental degradation